Acute neurology and neurophysiology of haemolytic–uraemic syndrome. Issue 5 (1st May 2001) - Eriksson, K J; Boyd, S G; Tasker, R C
Abstract : Involvement of the central nervous system (CNS) is found in around 30% of children with haemolytic–uraemic syndrome (HUS). This complication is the single most common cause of mortality and also a major contributor to the morbidity associated with HUS. We reviewed 22 children with HUS and acute CNS involvement. Both global and focal derangements occurred, and in survivors, early regional EEG abnormalities—especially those in the occipital and temporal areas—were prognostically useful.